2004
DOI: 10.1093/hmg/ddh135
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of FANCD2 with BRCA2 in DNA damage response pathways

Abstract: Fanconi anaemia (FA) is a chromosomal instability disorder characterized by cellular sensitivity to DNA interstrand crosslinking agents and a high risk of cancer. Six of the eight proteins encoded by the known FA genes form a nuclear complex which is required for the monoubiquitination of the FANCD2 protein. FANCD2 complexes and colocalizes with BRCA1, but its presumptive role in DNA repair has not yet been clearly defined. We used yeast two-hybrid analysis to test for interaction between FANCD2 and 10 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 57 publications
9
167
0
1
Order By: Relevance
“…However, it is possible that USP1 may regulate the levels of other monoubiquitinated substrates in DNA repair pathways. Recent studies by our group and others have found that FANCD2 and PCNA colocalize at DNA repair foci during certain conditions of replication stress 17,18 (and data not shown). Therefore, we explored whether USP1 can deubiquitinate PCNA -a monoubiquitinated protein that localizes and functions at the DNA replication fork after UV damage or replication arrest.…”
mentioning
confidence: 64%
“…However, it is possible that USP1 may regulate the levels of other monoubiquitinated substrates in DNA repair pathways. Recent studies by our group and others have found that FANCD2 and PCNA colocalize at DNA repair foci during certain conditions of replication stress 17,18 (and data not shown). Therefore, we explored whether USP1 can deubiquitinate PCNA -a monoubiquitinated protein that localizes and functions at the DNA replication fork after UV damage or replication arrest.…”
mentioning
confidence: 64%
“…Complex 1 is also essential for the inducible monoubiquitination of FANCD2 following cellular exposure to DNA damaging agents, such as MMC, ultraviolet (UV), or ionizing radiation (IR) and deoxynucleotide depletion due to hydroxyurea (Garcia-Higuera et al 2001;Gregory et al 2003). Following monoubiquitination, FANCD2 relocalizes from a soluble nuclear compartment to the chromatin fraction (Wang et al 2004) where it colocalizes in nuclear foci with other DNA damage response proteins, including FANCD1/BRCA2 (Hussain et al 2004;Wang et al 2004) BRCA1 (Garcia-Higuera et al 2001), RAD51 (Taniguchi et al 2002a;Hussain et al 2004), Proliferating Cell Nuclear Antigen (PCNA) (Hussain et al 2004), and Nijmegen Breakage Syndrome (NBS1) (Nakanishi et al 2002). Following relocalization to chromatin, monoubiquinated FANCD2 (FANCD2-Ub) promotes chromatin loading of the FANCD1/BRCA2 protein, forming a second complex (complex 2), where it may facilitate the formation of nuclear foci containing the homologous recombination (HR) DNA repair protein RAD51 (Wang et al 2004).…”
Section: The Basic Fa Pathwaymentioning
confidence: 99%
“…Accumulating evidence suggests a major function of complex 1 is to generate monoubiquitinated FANCD2 (FANCD2-Ub), required for the assembly of the FANCD2-Ub/BRCA2 chromatin complex (complex 2). Following monoubiquitination, FANCD2 relocalizes to DNA damage-induced S-phase foci where it associates with the DNA repair proteins BRCA2/FANCD1 (Wang (Nakanishi et al 2002), RAD51 (Hussain et al 2004), and PCNA (Howlett et al 2005). The formation of these DNA damage-induced FANCD2 foci is dependent on the presence of functional BRCA1 (Garcia-Higuera et al 2001), thereby linking this DNA repair protein to the FA pathway.…”
Section: The Structure Of the Fa Complexmentioning
confidence: 99%
“…FANCD2S+/FANCD2L+ phenotype in patients with a positive chromosome breakage test and FA clinical features suggests deleterious mutation on any of the genes functioning downstream of FANCD2 monoubiquitination. Three complementation groups corresponding to downstream proteins, that play their role after FANCD2 activation, have been identified (FANCD1/ BRCA2, FANCJ and FANCN) (9,15,19,28). Western blots for BRCA2 were performed on FANCD2S+/FANCD2L+ patients and all of them showed normal expression of this protein.…”
Section: Chromosome Breakage Test -Diepoxybutanementioning
confidence: 99%
“…The activation of this complex induced by DNA replication or by DNA-damage results in monoubiquitination of FANCD2, which moves into areas of damaged chromatin to interact with downstream FA members (FANCD1/BRCA2, FANCJ, FANCN) and other DNA-repair proteins such as BRCA1 and RAD51. FANCD2 is the central protein that connects the FA/BRCA pathway to the homologous recombination-mediated DNA repair (18,19,23,(25)(26)(27)(28). The recently identified FANCI protein associates with FANCD2 and is the second monoubiquitinated component of the FA pathway (14,29).…”
Section: Introductionmentioning
confidence: 99%